An assessment of the effectiveness of social media as a platform in library promotion of the UP School of Library and Information Studies - Valleza, Marc Almond J.
The UP School of Library and Information Studies Library is no exception in using social media to promote itself and its services to its users. However, engaging the users is not an easy feat. There are several factors that are attributed to the current reach of the library. The study seeks to assess how the library utilizes social media in its marketing and promotion and how effective these strategies are. Through an interview and focus group discussion, the study gathers both perspectives of the library and student users. Unique experiences of students provide a variety of reception, and the library also foresees early steps it could take for further improvements.